THE EFFECT OF NON-PHYSICAL WORK ENVIRONMENT AND WORK STRESS ON THE PERFORMANCE OF AUTO 2000 EMPLOYEES OF RADEN INTAN - Hendri Dunan; Jenita Sari (ZILLZELL MEDIA PRIMA, 2024)
The influence of the non-physical work environment and stress levels on employee performance are the main objectives of this research, especially in the organizational environment of Auto 2000 Raden Intan, a corporate entity operating in the automotive industry sector. This study used a quantitative approach. Because the non-physical work environment does not have a direct impact on the company but on employees if not managed properly, the relationship between employees and superiors is very important to achieve company goals. A total of 35 employees were included in the study population. The sample that took only the mechanical part was 35 employees from 111 total population at PT. Astra International Tbk. Auto 2000 Raden Intan. In the research analysis required to achieve this, multiple linear equations were used, and the results showed that work stress along with non-physical work environments can affect the good level of employee performance. The determinant coefficient R2 of 62.8% means that performance (Y) is affected by the non-physical work environment (X1) as well as work stress (X2) is 62.8%. While the remaining portion of 37.2% was influenced by additional components or variables outside this study.